A Dimeric Bis(melamine)‐Substituted Bispidine for Efficient Transmembrane H+/Cl− Cotransport. (9th March 2017) - Shinde, Sopan Valiba; Talukdar, Pinaki
Abstract: A 3, 7‐diazabicyclo[3.3.1]nonane linking to two melamines is a unique transmembrane H + /Cl − carrier. In the solid state, the V‐shaped compound forms a HCl‐bound zig‐zag network through cooperative protonation and hydrogen bond interactions. In the lipid membrane, the receptor forms a dimeric self‐assembly involving multiple H + and Cl − leading to the efficient transport of the acid. The pH‐dependent Cl − efflux observed for the compound was rationalized based on a gradual protonation model that confers an active transmembrane carrier at physiological pH.